Respostas

A melhor resposta!
2014-05-11T17:32:11-03:00
#  f(-1) = 1/2 - 1/3 + 1 ⇒ mmc(2,3) = 6 ⇒ (3 - 2 + 6)/6 = 7/6 ⇒  f(-1) = 7/6 
f(3/4) = 1/2 + 3/4/3 +(3/4)² ⇒  f(3/4) = 1/2+ 3/12 + 9/16 = 1/2 + 1/4 + 9/16  ⇒ 
mmc(2,4,16) = 16 ⇒  f(3/4) = (8 + 4 + 9)/16 = 13/16  ⇒  f(3/4) = 21/16
#  x = ?  f(x) = 1/2 ⇒ 1/2 + x/3 + x² = 1/2  ⇒ mmc(3,2) = 6  ⇒ 3 + 2x + 6x² = 3 ⇒
6x² + 2x = 0  ⇒ 3x² + x = 0  ⇒  x.(3x + 1) = 0 ⇒ Então,  x = 0 ou x = - 1/3

                                         Solução:  s = { 0 , -1/3 } 
2 5 2